(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The size of grinding media is the primary factor that affects the overall milling efficiency of a ball mill (e.g. power consumption and particle size breakage). This article tackles the lack of a design tool that could help choose the ball loading composition in mills. Such a tool enables the maximization of the exposed surface area per unit energy (cm2/J). The effect of ball load composition, by varying the grinding media size distribution (e.g. alternatively by mixing four groups of 19.5, 38 mm; 19.5, 50 mm; 38, 50 mm and 19.5, 38, 50 mm), on the milling efficiency of a laboratory scale ball mill has been investigated in this article concerning ball number, total surface area, and ball weight. The results reveal that the amount of required energy is close in values, per each ball loading mixture, concerning three characteristic parameters. The amount of required energy varies between 3.22 kWh/st & 3.65 kWh/st. Moreover, the new surface area per unit energy (e.g. cm2/J) significantly influences milling efficiency. In contrast, the ball weight has a minor effect. This study would be helpful in industries in which comminution is part of the process, such as mining and cement industries.